2017
DOI: 10.1097/pgp.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Biomarker Panel Increases the Reproducibility and the Accuracy in Endometrial Biopsy Diagnosis

Abstract: Grading and histologic typing of endometrial cancer in biopsy material has a direct impact on the decision to perform lymphadenectomy and/or omentectomy in many cancer centers. Endometrial biopsies are among the most common general surgical pathology specimens. Multiple studies have shown that biopsy diagnosis suffers from a lack of reproducibility. Although many biomarkers have been proposed, none have been demonstrated to improve the diagnosis in the biopsy setting. In this study, 70 biopsies with endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, one point worth mentioning is that a small percentage of low grade endometrioid adenocarcinomas contain TP53 mutations and exhibit mutation-type immunoreactivity. However, that being said, mutation-type p53 staining may be helpful in avoiding underdiagnosis of a serous carcinoma with intermediate grade nuclear features as grade 1 or 2 endometrioid carcinoma (3,20). Abnormal p53 staining alone is not sufficient for the differential diagnosis of endometrioid from serous carcinomas as a significant minority of grade 3 endometrioid carcinomas show mutation-type p53 immunoreactivity (21).…”
Section: Practical Uses Of P53 Immunohistochemistrymentioning
confidence: 99%
“…However, one point worth mentioning is that a small percentage of low grade endometrioid adenocarcinomas contain TP53 mutations and exhibit mutation-type immunoreactivity. However, that being said, mutation-type p53 staining may be helpful in avoiding underdiagnosis of a serous carcinoma with intermediate grade nuclear features as grade 1 or 2 endometrioid carcinoma (3,20). Abnormal p53 staining alone is not sufficient for the differential diagnosis of endometrioid from serous carcinomas as a significant minority of grade 3 endometrioid carcinomas show mutation-type p53 immunoreactivity (21).…”
Section: Practical Uses Of P53 Immunohistochemistrymentioning
confidence: 99%
“…When defining endometrioid features such as squamous or mucinous differentiation on a background of endometrial hyperplasia present, a diagnosis of endometrioid carcinoma can be rendered. The use of a panel of IHC stains can help to establish a confirmatory diagnosis when histomorphological findings are unclear or overlapping [6,9,15]. Biomarkers commonly used to distinguish between endometrioid and serous carcinomas are immunostaining for p53, p16, ER, PR, PTEN, and DNA mismatch repair proteins [6,9,12,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [8] demonstrated that a seven-marker immunostaining panel (consisting of estrogen receptor [ER], progesterone receptor [PR], p16, p53, vimentin, PTEN, and IGF2BP3) could differentiate high-grade endometrioid carcinoma and serous carcinoma with 100% concordance. Nastic et al [9] reported an increase in interobserver agreement rates after application of ER, PR, and p53 immunostaining and DNA ploidy studies. Molecular profiling can also aid in the differential diagnosis of endometrial carcinoma.…”
mentioning
confidence: 99%
“…The high-risk group includes women with type II EC, FIGO grade 3, and deep myometrial invasion/cervical stroma invasion according to ultrasound and/or magnetic resonance imaging [7]. All surgical treatment is performed based on the results of a diagnostic endometrial biopsy and radiological examinations, but the subjective nature of histology means that biopsy diagnoses often have poor reproducibility [8]. Moreover, histological features do not show the molecular properties of tumors, like abnormal genetic factors, epigenetic alterations, or environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, histological features do not show the molecular properties of tumors, like abnormal genetic factors, epigenetic alterations, or environmental factors. However, the heterogenic nature of many primary tumors makes proper molecular diagnosis difficult [8], which may explain why 20% of EC that develop into aggressive and metastatic cancer are first classified as nonaggressive [9]. The molecular characteristics of tumors need to be further investigated in order to address the limitations of the histopathological diagnosis of EC.…”
Section: Introductionmentioning
confidence: 99%